Socio-demographic characteristics of patients with familial hypercholesterolemia in Almaty, Kazakhstan - Kairat Davletov; Indira Baibolsynova; Sergey Lee; Mukhtar Kulimbet (Modern Scientific Technology, 2025)
Familial hypercholesterolemia (FH) is a common inherited disorder of lipid metabo-lism characterized by lifelong elevated low-density lipoprotein cholesterol (LDL-C) levels and a significantly increased risk of premature cardiovascular disease (CVD) [1]. Esti-mates of FH prevalence are approximately 0.26–0.39% of the general population (roughly 1 in 313 individuals) worldwide [2,3], making it one of the most prevalent genetic condi-tions. There is some geographic and ethnic variation in reported prevalence. For example, studies in Europe have noted higher rates in certain populations – up to about 1 in 192 in a Spanish cohort [4] and 1 in 137 in a Danish [5] sample using clinical criteria. These dif-ferences may reflect founder effects, population demographics, or varying diagnostic cri-teria. Nevertheless, across regions the prevalence of FH in those with established heart disease is dramatically higher, roughly 1 in 16 patients with coronary artery disease [3]. This highlights the substantial contribution of undiagnosed FH to premature atheroscle-rosis globally. Despite its frequency and clinical significance, most individuals with FH remain unidentified and untreated. It is estimated that less than 1% of FH cases are currently rec-ognized in most countries [6]. Moreover, even among those diagnosed with FH, many do not receive adequate therapy to achieve recommended LDL-C targets [7]. The reasons in-clude lack of awareness, insufficient screening (for example, cholesterol screening in chil-dren or cascade testing of relatives is not routinely implemented in many settings), and limited access to potent lipid-lowering therapies in some regions [8]. Early diagnosis and aggressive treatment of FH (with high-intensity statins, ezetimibe, PCSK9 inhibitors) can dramatically improve outcomes. Dietary and lifestyle measures alone are usually insuffi-cient to counteract the extreme LDL elevation in FH. Therefore, identifying individuals with FH and instituting therapy early is a public health priority. To date, there is a notable gap in the epidemiological data on FH in Central Asia. Most prevalence studies have been conducted in Europe, North America, East Asia, and Australia, whereas regions such as South/Central Asia and Africa are under-studied [6]. Kazakhstan, a large Central Asian nation, has lacked published data on the burden of FH. The present study aims to address this gap by examining the prevalence of FH in Almaty region among adults in Kazakhstan and evaluating their lipid profiles, cardiovascular comorbidities, and treatment patterns.